Clinical and microbiological efficacy of three different treatment methods in the management of denture stomatitis - ÖZKAN, YASEMİN (WILEY, 2011)
Objective: This study evaluated. the effect of mouthrinses and tissue conditioner on the clinical findings and microbial flora of 60 patients with Newton's type II denture stomatitis (N2DS) Background: Denture stomatitis is a common problem in complete denture wearers. Materials and methods: Sixty patients with N2DS were included in this study and divided into three groups. Two groups of patients were instructed to rinse their mouth with the designated mouthrinses DioxiDent and Corsodyl twice daily for 1 min and to soak their dentures overnight in these solutions for 15 days. For the third group, tissue conditioner was placed in each of 20 patients' existing maxillary dentures. Patients were evaluated both clinically and microbiologically at baseline and after 15 days. Palatal swabs and smears were taken from each patient before and after treatment and these samples were examined mycologically. The difference between Candida colonisation before and after treatment and the differences between pre-treatment and post-treatment clinical findings were assessed. Results: DioxiDent and Corsodyl showed an improvement in palatal inflammation and a decrease in Candida colonisation compared to Visco-gel. Conclusions: The effectiveness of topical chlorine dioxide and chlorhexidine gluconate in the management of N2DS was demonstrated.
Keywords: denture stomatitis; Candida albicans; complete denture; denture cleansing; denture hygiene; CANDIDA-ALBICANS; IN-VITRO; ANTIFUNGAL; GROWTH; CHLORHEXIDINE; PLAQUE